The role of organizational context in moderating the effect of research use on pain outcomes in hospitalized children: a cross sectional study. Issue 1 (December 2017) - Yamada, Janet; Squires, Janet; Estabrooks, Carole; Victor, Charles; Stevens, Bonnie
Abstract Background Despite substantial research on pediatric pain assessment and management, health care professionals do not adequately incorporate this knowledge into clinical practice. Organizational context (work environment) is a significant factor in influencing outcomes; however, the nature of the mechanisms are relatively unknown. The objective of this study was to assess how organizational context moderates the effect of research use and pain outcomes in hospitalized children. Methods A cross-sectional survey was undertaken with 779 nurses in 32 patient care units in 8 Canadian pediatric hospitals, following implementation of a multifaceted knowledge translation intervention, Evidence-based Practice for Improving Quality (EPIQ). The influence of organizational context was assessed in relation to pain process (assessment and management) and clinical (pain intensity) outcomes. Organizational context was measured using the Alberta Context Tool that includes: leadership, culture, evaluation, social capital, informal interactions, formal interactions, structural and electronic resources, and organizational slack (staff, space, and time). Marginal modeling estimated the effects of instrumental research use (direct use of research knowledge) and conceptual research use (indirect use of research knowledge) on pain outcomes while examining the effects of context. Results Six of the 10 organizational context factors (culture, social capital, informal interactions, resources, and organizational slack [space and time]) significantly moderated the effect of instrumental research use on pain assessment; four factors (culture, social capital, resources and organizational slack time) moderated the effect of conceptual research use and pain assessment. Only two factors (evaluation and formal interactions) moderated the effect of instrumental research use on pain management. All organizational factors except slack space significantly moderated the effect of instrumental research use on pain intensity; informal interactions and organizational slack space moderated the effect of conceptual research use and pain intensity. Conclusions Many aspects of organizational context consistently moderated the effects of instrumental research use on pain assessment and pain intensity, while only a few influenced conceptual use of research on pain outcomes. Organizational context factors did not generally influence the effect of research use on pain management. Further research is required to further explore the relationships between organizational context and pain management outcomes.